Injury Research Theories, Methods, and Approaches - Li, Guohua; Baker, Susan P. (Springer US : Imprint: Springer, 2012)
Injury Research Theories, Methods, and Approaches Guohua Li and Susan Baker, editors   From the long-held popular belief, "accidents will happen," it is now recognized that this needn't be the case. More and more, injury is being seen as no accident, not only predictable, but preventable-and an important public health issue requiring rigorous study and multiple levels of intervention.   To this end, Injury Research: Theories, Methods, and Approaches assembles a team of multidisciplinary experts from around the globe. Early chapters provide a solid foundation for gathering injury data and monitoring trends. Research methods and injury-reduction approaches gleaned from public health, medicine, engineering, behavioral science, and other areas demonstrate both the intricacies of causation and the potential for intervention. The result is an authoritative and comprehensive textbook relevant for anyone planning to enter a career in injury control and prevention.   Featured in the coverage:   ·         Methodological and technical issues in injury surveillance ·         Concepts and methods for understanding causes of injury, from epidemiology to ergonomics to forensic pathology ·         Methods and theories in measuring injury severity and for improving survival and functional outcomes, from patient triage to clinical prognosis to economic valuation ·         Statistical methods and modeling techniques particularly well-suited for injury data analysis ·         Multidisciplinary perspectives on injury control and program evaluation       Injury Research is a bedrock text for graduate students studying injury and violence epidemiology as part of a Master's in Public Health program.  Graduate students in related fields including emergency medicine, biomechanical engineering, transportation safety, urban planning, risk assessment, and criminal justice will find this book an important reference as well.   "The first textbook that comprehensively presents the theories and methods of injury research - from the way ergonomics can reduce injuries to the effect of trauma-center systems on an injured person's chances of survival." - New York Times.